Longitudinal bidirectional associations between personality and becoming a leader - Eva Asselmann; Elke Holst; Jule Specht (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
Objective: Leaders differ in their personalities from non-leaders. However, when do these differences emerge? Are leaders "born to be leaders" or does their personality change in preparation for a leadership role and due to increasing leadership experience? Method: Using data from the German Socio-Economic Panel Study, we examined personality differences between leaders (N = 2683 leaders, women: n = 967; 36.04%) and non-leaders (N = 33,663) as well as personality changes before and after becoming a leader. Results: Already in the years before starting a leadership position, leaders-to-be were more extraverted, open, emotionally stable, conscientious, and willing to take risks, felt to have greater control, and trusted others more than non-leaders. Moreover, personality changed in emergent leaders: While approaching a leader-ship position, leaders-to-be (especially men) became gradually more extraverted, open, and willing to take risks and felt to have more control over their life. After becoming a leader, they became less extraverted, less willing to take risks, and less conscientious but gained self-esteem. Conclusions: Our findings suggest that people are not simply "born to be leaders" but that their personalities change considerably in preparation for a leadership role and due to leadership experience. Some changes are transient, but others last for a long time.
Keywords: 330; Big Five; development; leadership; manager; occupational success